The origins of banana-fibre cloth in the Ryukyus, Japan - Hendrickx, Katrien (Studia anthropologica., 2007)
Studia Anthropologica 12The Japanese word bashofu literally means ""banana-fiber cloth."" Both the cloth and the clothing made from it are now considered important constituents of Okinawan identity. The Japanese Folk Craft Movement in the 1930s brought attention to this special trait of Okinawan material culture. After years of decline following World War II, the weaving and use of bashofu saw a revival that accelerated after the return of Okinawa to Japan in 1972 and still continues. Although today bashofu receives considerable attention because of its status since 1974 as one of Japan''s imp